Pre-operative physiotherapy for anaesthetised children with cystic fibrosis : a pilot study to assess the immediate and longer-term effects on respiratory function - Tannenbaum, Esta-Lee (Division of Physiotherapy, 2014)
Bibliography: leaves 63-71.